Perilaku Konsumtif Remaja Perempuan ditinjau dari Konformitasdan Persepsiterhadap Produk Makeup Korea - Hidayati, Ira; Supriyati, Supriyati; Lestari, Adelia Putri (ANFUSINA: Journal of Psychology, 2021)
AbstractConsumptive behavior is a lifestyle of consumers in society who tend to perceive material as something that can bring satisfaction in itself, this lifestyle can lead to consumptiveism. Consumptive behavior is influenced by several factors such as social factors and psychological factors which consist of conformity and perception, which will be used as factors that influence consumptive behavior in this study. This study aims to determine the relationship between conformity and perception with consumptive behavior towards Korean make-up products in the DMC Project community. The hypothesis proposed by the researcher is first: there is a relationship between conformity and perceptions of consumptive behavior, second: there is a relationship between conformity and consumptive behavior, third: there is a relationship between perception and consumptive behavior. The research method used in this research is quantitative method with non-random sampling technique, namely purposive sampling with a total of 60 subjects. This study used three scales to collect data including the consumptive behavior scale with 21 items (α = 0.961), the conformity scale with 24 items (α = 0.960) and the perception scale with 18 items (α = 0.931). The data obtained were then processed using multiple linear regression analysis techniques assisted by the SPSS 25.0 for windows program. The results showed first, the result of R = 0.838 and the value of F = 67, 039 with p = 0.000 (p <0.01), which means there is a correlation between conformity and perception simultaneously with consumptive behavior. Second, the value of t = 8,422 and p = 0.000 (p <0.01) means that there is a relationship between conformity and consumptive behavior. Third, t = -0.564 and p = 0.575 (p <0.01) means that there is no relationship between perceptions of consumptive behavior.Keywords: Consumptive behavior, conformity, Korean make-up products